Chronic Energy Deficiency (CED) Prediction Model in Adolescent Females (10-19 Years) In Indonesia - Kezia, Agnes Alya; Kalsum, Ummi; Guspianto, Guspianto (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Chronic Energy Deficiency (CED) in Indonesia has not yet reached an acceptable threshold. CED among adolescent girls can be caused by both direct and indirect factors. This research was conducted to develop a predictive model for the incidence of CED among adolescent girls (aged 10–19 years) in Indonesia. This study is a secondary research using a cross-sectional design. The data were obtained from the 2023 SKI dataset, with a sample of 55,506 adolescent girls aged 10–19 years. The data analysis was conducted using Complex Samples Chi-Square and Cox Regression predictive modeling. The study found that the proportion of CED among adolescent girls in Indonesia was 46.2%. The most dominant factor influencing CED among adolescent girls is age (PR = 1.430; 95% CI: 1.367–1.495), indicating that girls aged 10–14 years were at a higher risk of experiencing CED compared to those aged 15–19 years. Therefore, it is recommended that adolescent girls, especially those aged 10–14 years, maintain healthy behaviors, do a physical activity, and eat a lot of fruit and vegetable.